Simulasi Pembelajaran Terpadu Model Fragmented - Esa Eryani; Ila Mustakimah; Nia Octaviani; Sulastri Banyutresna (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Before entering school, children are used to seeing and studying all the events that occur around them or what they experience as a holistic whole, they do not see all of it partially (separately). The purpose of this integrated learning as a concept is a learning approach that involves several subjects to provide a meaningful learning experience for children. Integrated learning is believed to be an approach that is oriented towards learning practices that suit the needs of children. Effective integrated learning will help create broad opportunities for children to see and build interrelated concepts. The method we use is the approach method where we link ideas in various subjects. From the method that we apply, we can get a lot of teaching to our students, from the social emotional aspect of the child, the physical aspect of gross and fine motor skills, the artistic aspect and many others.